Construction of 1,2,3-Triazole-Embedded Polyheterocyclic Compounds via CuAAC and C–H Activation Strategies - Antonia Iazzetti; Dario Allevi; Giancarlo Fabrizi; Yuri Gazzilli; Antonella Goggiamani; Federico Marrone; Francesco Stipa; Karim Ullah; Roberta Zoppoli (Molecules, 2025)
Over the past two decades, the copper(I)-catalyzed azide–alkyne 1,3-dipolar cycloaddition (CuAAC), commonly known as click chemistry, and C–H bond activation have gained significant attention and have emerged as key synthetic methodologies. In our efforts to synthesize fused nitrogen-containing heterocycles, we developed a palladium-catalyzed protocol for the synthesis of functionalized 7,10-dihydropyrrolo[3,2,1-ij][1,2,3]triazolo[4,5-c]quinolines and 5,8-dihydrobenzo[3,4][1,2,3]triazolo[4′,5′:5,6]azepino[1,2-a]indoles from suitable bromo-substituted N-propargyl-indoles. The reaction conditions demonstrate broad functional group compatibility including halogen, alkoxyl, cyano, ketone, and ester, affording the target compounds in good to high yields.